Two-component curing composition set, thermally conductive cured product, and electronic device
Patent Information
- Application Number
- JP2022555438
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-05
- Filing Date
- 2021-10-01
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-10-01
AI Technical Summary
【0016】 本発明によれば、硬化反応に湿気が不要で、均一硬化性が高く、また、白金触媒を必要とせず、硬化阻害が生じにくい二液硬化型組成物セット、及び当該二液硬化型組成物セットから得られる硬化物または熱伝導性硬化物、並びに当該熱伝導性硬化物を備える電子機器を提供することが可能となる。
Smart Images

Figure 0007629935000001 
Figure 0007629935000002 
Figure 0007629935000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a two-component curing composition set, a thermally conductive cured product, and an electronic device. [Background technology]
[0002] Room temperature curing liquid silicone rubber exhibits stable performance over a wide temperature range, and is therefore used to improve the reliability of electrical and electronic equipment, such as computer CPUs (central processing units), car batteries, and LED devices.Specifically, it is used as an encapsulant, sealing material, potting material, coating material, and heat dissipation material for various electronic substrates.
[0003] Room temperature curing liquid silicone rubbers are mainly classified into one-component and two-component types, and the two-component type is further divided into condensation reaction type and addition reaction type.
[0004] The condensation reaction type is cured by the moisture in the air, and can exhibit excellent adhesion to various substrates that come into contact with it during curing. In particular, compositions that are cured by dealcoholization condensation using a titanium-based condensation reaction catalyst do not emit unpleasant odors or corrode metals during curing, making them suitable for use as sealing materials or coating materials for electrical and electronic devices.
[0005] On the other hand, the condensation reaction type cures gradually from the part that comes into contact with moisture in the air, so it takes a long time to cure uniformly. In addition, since outgassing is generated during the curing process, it is unsuitable for sealed applications.
[0006] The addition reaction type has a low shrinkage rate due to curing, has high uniform reactivity, and does not generate outgassing, making it suitable for use as a sealing material or heat dissipation material in electric and electronic devices.
[0007] On the other hand, the addition reaction type requires a platinum catalyst, which is a precious metal, but platinum catalysts are sensitive to temperature, and there is a problem that the catalytic activity is lost during transportation in a high-temperature environment. In addition, there is a problem that the presence of curing inhibitors such as nitrogen-containing compounds, sulfur-containing compounds, phosphorus-containing compounds, tin-containing compounds, sulfur, solder flux, alcohol, water, carboxylic acid, etc. on the substrate causes poor curing.
[0008] As described above, the condensation reaction type and the addition reaction type each have advantages and disadvantages, and are used depending on the application and purpose. In addition, improvements to overcome the disadvantages have been reported.
[0009] For example, Patent Document 1 describes a composition that cures uniformly without cure inhibition and has excellent adhesive properties, the composition comprising a mixture of an organopolysiloxane containing an alkoxy group and an organopolysiloxane containing a lower alkenyl group, an organopolysiloxane containing silicon-bonded hydrogen atoms, an alkoxysilane, and a catalyst for a hydrosilylation reaction.
[0010] Patent Document 2 describes an addition reaction type silicone rubber composition that is less susceptible to the effects of cure inhibitors and has excellent adhesive properties, thanks to a composition consisting of an alkenyl group-containing organopolysiloxane, an organohydrogenpolysiloxane, a platinum catalyst, and an adhesion promoter.
[0011] Furthermore, Patent Documents 3 and 4 disclose resin compositions made from a silicone-modified epoxy resin and a silicone compound having a reactive functional group as silicone-based compositions other than the above-mentioned condensation reaction type and addition reaction type. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] Japanese Patent Application Publication No. 8-269337 [Patent Document 2] JP 2006-22284 A [Patent Document 3] Japanese Patent Application Publication No. 10-017776 [Patent Document 4] Japanese Patent Application Publication No. 55-90554 Summary of the Invention [Problem to be solved by the invention]
[0013] As mentioned above, both the two-part condensation reaction type and the two-part addition reaction type liquid silicone rubbers have their own advantages and disadvantages, and there has been a demand for the development of a room temperature curing liquid silicone rubber that overcomes the disadvantages of both types.
[0014] The present invention has been made in consideration of the above problems, and has an object to provide a two-component curing composition set that does not require moisture for the curing reaction, has high uniform curing properties, does not require a platinum catalyst, and is less susceptible to curing inhibition, a cured product or thermally conductive cured product obtained from the two-component curing composition set, and an electronic device equipped with the thermally conductive cured product. [Means for solving the problem]
[0015] That is, the present invention is as follows. [1] A first agent including an epoxy-modified organopolysiloxane A1 having an epoxy group-containing group and a thermally conductive filler B1; A second agent including an amino-modified organopolysiloxane A2 having an amino group-containing group and a thermally conductive filler B2; Two-part curing composition set. [2] the functional group equivalent weight of the epoxy group in one molecule of the epoxy-modified organopolysiloxane A1 is 100 to 11,000 g / mol; The two-component curing composition set according to [1]. [3] the functional group equivalent weight of the amino group in one molecule of the amino-modified organopolysiloxane A2 is 100 to 8000 g / mol; The two-component curing composition set according to [1] or [2]. [4] The amino-modified organopolysiloxane A2 in the second agent has hydroxyl group-containing groups at both ends. The two-component curing composition set according to any one of [1] to [3]. [5] The thermally conductive filler B1 and the thermally conductive filler B2 each contain at least one selected from the group consisting of aluminum oxide, aluminum nitride, boron nitride, silicon nitride, zinc oxide, aluminum hydroxide, metallic aluminum, magnesium oxide, copper, silver, and diamond, each of which has a thermal conductivity of 10 W / m·K or more. The two-component curing composition set according to any one of [1] to [4]. [6] The first agent does not contain an organopolysiloxane having at least a vinyl group at the end or in a side chain, and an organopolysiloxane having at least a hydrosilyl group at the end or in a side chain; and The second agent is provided with an organopolysiloxane having at least a vinyl group at the end or in a side chain, and the second agent does not include an organopolysiloxane having at least a hydrosilyl group at the end or in a side chain. The two-component curing composition set according to any one of [1] to [5]. [7] The thermal conductivity of the mixture of the first agent and the second agent after curing is 1.0 W / mk or more, as measured in accordance with ASTM D5470. The two-component curing composition set according to any one of [1] to [6]. [8] Used as a thermally conductive heat dissipation material, The two-component curing composition set according to any one of [1] to [7]. [9] [1] to [8], wherein the two-component curing composition set is obtained from a mixture of the first agent and the second agent. cured product.
[10] Used as a thermally conductive heat dissipation material, The cured product according to [9].
[11] An electronic component, the cured product according to
[10] , and a housing that accommodates the electronic component and the cured product, The electronic component and the housing are in contact with each other via the cured product. electronic equipment. Effect of the Invention
[0016] According to the present invention, it is possible to provide a two-component curing composition set that does not require moisture for the curing reaction, has high uniform curing properties, does not require a platinum catalyst, and is less susceptible to curing inhibition, as well as a cured product or thermally conductive cured product obtained from the two-component curing composition set, and an electronic device equipped with the thermally conductive cured product. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, an embodiment of the present invention (hereinafter, referred to as "the present embodiment") will be described in detail. However, the present invention is not limited to the following embodiment, and various modifications are possible without departing from the gist of the present invention.
[0018] [Two-component curing composition set] The two-component curing composition set according to this embodiment comprises a first agent containing an epoxy-modified organopolysiloxane A1 having an epoxy group-containing group and a thermally conductive filler B1, and a second agent containing an amino-modified organopolysiloxane A2 having an amino group-containing group and a thermally conductive filler B2.
[0019] Conventional two-component curing silicone compositions utilize condensation reactions or addition reactions. However, condensation reactions using organopolysiloxanes having hydroxyl groups or alkoxy groups require moisture for curing, generate reaction by-products (outgassing), and have problems such as high shrinkage. On the other hand, addition reactions using organopolysiloxanes having vinyl groups and organopolysiloxanes having hydrosilyl groups have excellent shrinkage, do not generate outgassing, and do not require moisture, but require an addition reaction catalyst such as a platinum catalyst, and have problems such as curing inhibition caused by coexisting compounds.
[0020] In contrast, in the present embodiment, by using the epoxy-modified organopolysiloxane A1 having an epoxy group-containing group and the amino-modified organopolysiloxane A2 as described above, it is possible to provide a two-component curing composition set that does not require an addition reaction catalyst such as a platinum catalyst, does not cause curing inhibition, does not require moisture for curing, and does not generate outgassing.
[0021] Furthermore, for the reasons described above, in this embodiment, it is preferable that neither the first agent nor the second agent contains an organopolysiloxane having a vinyl group at least at the end or in a side chain, nor an organopolysiloxane having a hydrosilyl group at least at the end or in a side chain.
[0022] Each component contained in the first and second agents will be described in detail below.
[0023] <First agent> The first agent contains an epoxy-modified organopolysiloxane A1 having an epoxy group-containing group, and a thermally conductive filler B1, and may contain additives such as polydimethylsiloxane C, organosilane D, and colorant E, as necessary.
[0024] (Epoxy modified organopolysiloxane A1) The epoxy-modified organopolysiloxane A1 of this embodiment has a substituent (epoxy group-containing group) having an epoxy group at the end or in the side chain. The organopolysiloxane having an epoxy group is one in which at least a part of the R in the Si-R portion (wherein R is a substituted or unsubstituted monovalent hydrocarbon group) in the organopolysiloxane molecule is a substituent having an epoxy group.
[0025] The epoxy group-containing group is not particularly limited, but examples thereof include an aliphatic epoxy group represented by the following formula (a11) and an alicyclic epoxy group represented by the following formula (a12). Among these, an aliphatic epoxy group such as a glycidyl group is preferred from the viewpoint of curing reactivity, and an alicyclic epoxy group such as an ethylcyclohexene oxide group is preferred from the viewpoint of increasing the glass transition point of the obtained cured product. The epoxy-modified organopolysiloxane A1 may have both an aliphatic epoxy group and an alicyclic epoxy group. [ka] (In the formula, R 1 represents an alkyl group having 1 to 6 carbon atoms.
[0026] The epoxy-modified organopolysiloxane A1 may have any of a linear structure, a branched structure, and a cyclic structure, and may have a structure in which a linear structure and a cyclic structure are combined, or a structure in which a branched structure and a cyclic structure are combined. Among these, a linear structure is preferred from the viewpoint of handling as a liquid, and a branched structure is preferred from the viewpoint of the mechanical properties of the obtained cured product.
[0027] The bonding position of the epoxy group-containing group in the epoxy-modified organopolysiloxane A1 is not particularly limited, and may be a terminal or a side chain, or may be a terminal and a side chain. When the epoxy group-containing group is present in the side chain, the epoxy-modified organopolysiloxane A1 has, for example, a structural unit represented by the following general formula (a1-1) or (a1-2). When the epoxy group-containing group is present in the terminal, the epoxy-modified organopolysiloxane A1 has, for example, a terminal structure represented by the following general formula (a1-3) (wherein n is 1 or more). Furthermore, as a structural unit to which an epoxy group-containing group is not bonded, a structural unit represented by the following general formula (a1-4) can be given. The structural units that the epoxy-modified organopolysiloxane A1 has are not limited to the following, and for example, when the epoxy-modified organopolysiloxane A1 has a branched structure, it may have a branched structural unit, and when the epoxy-modified organopolysiloxane A1 has a cyclic structure, it may not have a terminal structure. [ka] (In the formula, each X independently represents an epoxy group-containing group; R 2 each independently represents a substituted or unsubstituted hydrocarbon group or polyether group having 1 to 12 carbon atoms, and n represents an integer of 0 to 3.
[0028] R 2 The substituted or unsubstituted hydrocarbon group represented by the formula (I) is not particularly limited, and examples thereof include alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, and dodecyl groups; cycloalkyl groups such as cyclopentyl and cyclohexyl groups; aryl groups such as phenyl, tolyl, xylyl, and naphthyl groups; aralkyl groups such as benzyl, 2-phenylethyl, and 2-phenylpropyl groups; and halogenated alkyl groups such as chloromethyl, 3,3,3-trifluoropropyl, and 3-chloropropyl groups.
[0029] Also, R 2 The polyether group represented by the formula (I) is not particularly limited, but may be, for example, a polyethylene glycol group (-(C2H4O) l -CH2H5,-(C2H4O) l -CH2H4OH), polypropylene glycol group (-(C3H6O) l -CH3H7,-(C3H6O) l —CH3H6OH), and polyethylene glycol-polypropylene glycol copolymer group. Here, l represents an integer of 2 to 1000.
[0030] Among these, the epoxy-modified organopolysiloxane A1 is preferably an organopolysiloxane having a linear structure and an epoxy-containing group in the side chain. By using such an epoxy-modified organopolysiloxane A1, the reactivity of the first agent and the second agent tends to be further improved.
[0031] The epoxy functional group equivalent of the epoxy-modified organopolysiloxane A1 is preferably 100 to 11000 g / mol, more preferably 200 to 6000 g / mol, and even more preferably 250 to 5000 g / mol. When the epoxy functional group equivalent is within the above range, the reactivity of the first agent and the second agent is improved, and the uniform reactivity tends to be improved.
[0032] The viscosity of the epoxy-modified organopolysiloxane A1 at 25° C. is preferably 5 to 15,000 mm 2 / s, and more preferably 5 to 12000 mm 2 / s, and more preferably 5 to 10,000 mm 2 When the viscosity is within the above range, the handleability of the two-component curing composition set tends to be improved.
[0033] (Thermal conductive filler B1) The thermally conductive filler B1 is, for example, a filler having a thermal conductivity of at least 10 W / m·K. Although there are no particular limitations on such thermally conductive filler B1, examples thereof include aluminum oxide (hereinafter also referred to as "alumina"), aluminum nitride, silica, boron nitride, silicon nitride, zinc oxide, aluminum hydroxide, metallic aluminum, magnesium oxide, diamond, carbon, indium, gallium, copper, silver, iron, nickel, gold, tin, metallic silicon, and the like.
[0034] Among these, it is preferable to include at least one selected from the group consisting of aluminum oxide, aluminum nitride, boron nitride, silicon nitride, zinc oxide, aluminum hydroxide, metallic aluminum, magnesium oxide, copper, silver, and diamond, and alumina is more preferable. By using such a thermally conductive filler B1, the filling property is improved, and the thermal conductivity of the obtained cured product tends to be further improved. These thermally conductive fillers B1 may be used alone or in combination of two or more.
[0035] The thermally conductive filler B1 has an average particle size of preferably 0.1 to 120 μm, and more preferably 0.1 to 60 μm. When the average particle size of the thermally conductive filler B1 is within the above range, the fluidity, dispersibility, and filling property tend to be further improved.
[0036] The thermally conductive filler B1 may be a mixture of fillers having different average particle sizes. For example, it is more preferable to use a combination of a thermally conductive filler (B1-1) having an average particle size of 40 to 50 μm and a thermally conductive filler (B1-2) having an average particle size of 1 to 10 μm. In this case, the content of the thermally conductive filler (B1-1) is preferably 40 to 80 mass%, more preferably 50 to 70 mass%, based on the total amount of the thermally conductive filler B1. The content of the thermally conductive filler (B1-1) is preferably 20 to 60 mass%, more preferably 30 to 50 mass%, based on the total amount of the thermally conductive filler B1. By using such a thermally conductive filler B1, the fluidity, dispersibility, and filling property tend to be further improved. The average particle size in this embodiment means D50 (median diameter).
[0037] The content of the thermally conductive filler B1 is preferably 400 to 3000 parts by weight, more preferably 600 to 2800 parts by weight, and even more preferably 700 to 2600 parts by weight, relative to 100 parts by weight of the epoxy-modified organopolysiloxane A1. When the content of the thermally conductive filler is 400 parts by weight or more relative to 100 parts by weight of the epoxy-modified organopolysiloxane A1, the thermal conductivity of the obtained cured product becomes better, and when it is 3000 parts by weight or less, the decrease in fluidity can be more effectively suppressed and the coatability can be ensured.
[0038] (Polydimethylsiloxane C) Polydimethylsiloxane C can be added to adjust the viscosity of the first agent and the hardness of the resulting cured product. The viscosity of the polydimethylsiloxane is not particularly limited, and multiple types of polydimethylsiloxanes with different viscosities may be used in combination.
[0039] The content of polydimethylsiloxane C is preferably 0 to 80 parts by weight per 100 parts by weight of the total of the epoxy-modified organopolysiloxane A1 and polydimethylsiloxane.
[0040] (Organosilane D) Organosilane D can be added to adjust the wettability between the thermally conductive filler B1 and the epoxy-modified organopolysiloxane A1. Although there is no particular limitation on such organosilane, for example, an organosilane represented by the following general formula (d) is preferably used. R 3 a R 4 b Si(OR 5 ) 4-(a+b) (d) (In the formula, R 3 each independently represents an alkyl group having 1 to 15 carbon atoms; R 4 each independently represents an unsaturated monovalent hydrocarbon group having 1 to 8 carbon atoms; R 5 each independently represents an alkyl group having 1 to 6 carbon atoms, a is an integer of 1 to 3, b is an integer of 0 to 2, and a+b is an integer of 1 to 3.
[0041] In formula (d), R 3 The alkyl group having 1 to 15 carbon atoms represented by is not particularly limited, but examples thereof include a methyl group, an ethyl group, a propyl group, a hexyl group, a nonyl group, a decyl group, a dodecyl group, a tetradecyl group, a 3,3,3-trifluoropropyl group, a 2-(perfluorobutyl)ethyl group, and a 2-(perfluorooctyl)ethyl group. 3 is preferably an alkyl group having 6 to 12 carbon atoms.
[0042] R 4The unsaturated monovalent hydrocarbon group having 1 to 8 carbon atoms represented by is not particularly limited, and examples thereof include alkenyl groups such as vinyl group, allyl group, etc.; aryl groups such as phenyl group, tolyl group, etc.; aralkyl groups such as 2-phenylethyl group, 2-methyl-2-phenylethyl group, etc.; and halogenated hydrocarbon groups such as p-chlorophenyl group.
[0043] R 5 The alkyl group having 1 to 6 carbon atoms represented by is not particularly limited, but examples thereof include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, and a hexyl group. 5 is preferably a methyl group or an ethyl group.
[0044] a is an integer of 1 to 3, and preferably 1. b is an integer of 0 to 2, and preferably 0. a+b is an integer of 1 to 3, and preferably 1.
[0045] The content of the organosilane D is preferably 0.01 to 30 parts by weight, more preferably 0.1 to 5.0 parts by weight, based on 100 parts by weight of the epoxy-modified organopolysiloxane A1. When the content of the organosilane D is within the above range, the wettability can be effectively improved.
[0046] (Colorant E) There is no particular limitation on the colorant E, and examples thereof include any pigment. There is no particular limitation on the content of colorant E, and for example, it is preferably 0.05 to 0.2 parts by weight with respect to 100 parts by weight in total of the first agent and the second agent described below.
[0047] <Second Agent> The second agent contains an amino-modified organopolysiloxane A2 having an amino group-containing group and a thermally conductive filler B2, and may contain additives such as polydimethylsiloxane C, organosilane D, and colorant E, as necessary.
[0048] (Amino-modified organopolysiloxane A2) The amino-modified organopolysiloxane A2 of this embodiment has a substituent (amino group-containing group) having an amino group at the end or in the side chain. The organopolysiloxane having an amino group is one in which at least a part of the R in the Si-R portion (wherein R is a substituted or unsubstituted monovalent hydrocarbon group) in the organopolysiloxane molecule is a substituent having an amino group.
[0049] The amino group-containing group is not particularly limited, and examples thereof include the amino group represented by the following formula (a21): Such an amino group-containing group may be a primary amino group or a secondary amino group, and among these, R 6 is preferably a primary amino group in which R is a hydrogen atom. [ka] (In the formula, R 6 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, the hydrogen atom of which may be substituted with an amino group; R 7 represents an alkyl group having 1 to 6 carbon atoms.
[0050] R 6 R represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, the hydrogen atom of which may be substituted with an amino group. 6 When R is a hydrogen atom, the amino group represented by formula (a21) has a primary amino group at the terminal, such as a 3-aminopropyl group. 6 When R is an alkyl group having 1 to 6 carbon atoms, the amino group represented by formula (a21) has a secondary amino group. 6 When the alkyl group represented by formula (a21) is an alkyl group having 1 to 6 carbon atoms in which a hydrogen atom is substituted with an amino group, the amino group represented by formula (a21) is a group having a primary amino group and a secondary amino group, such as an aminoethylaminopropyl group, a group having multiple primary amino groups, or a group having multiple secondary amino groups.
[0051] The amino-modified organopolysiloxane A2 may have any of a linear structure, a branched structure, and a cyclic structure, and may have a structure in which a linear structure and a cyclic structure are combined, or a structure in which a branched structure and a cyclic structure are combined. Among these, a linear structure is preferred from the viewpoint of handling as a liquid, and a branched structure is preferred from the viewpoint of the mechanical properties of the obtained cured product.
[0052] The bonding position of the amino group-containing group in the amino-modified organopolysiloxane A2 is not particularly limited, and may be a terminal or a side chain, or may be a terminal and a side chain. When the amino group-containing group is present in the side chain, the amino-modified organopolysiloxane A2 has, for example, a structural unit represented by the following general formula (a2-1) or (a2-2). When the amino group-containing group is present in the terminal, the amino-modified organopolysiloxane A2 has, for example, a terminal structure represented by the following general formula (a2-3) (wherein m is 1 or more). Furthermore, as a structural unit to which an amino group-containing group is not bonded, a structural unit represented by the following general formula (a2-4) can be given. The structural units that the amino-modified organopolysiloxane A2 has are not limited to the following, and for example, when the amino-modified organopolysiloxane A2 has a branched structure, it may have a branched structural unit, and when the amino-modified organopolysiloxane A2 has a cyclic structure, it may not have a terminal structure. [ka] (In the formula, each Y independently represents an amino group-containing group; R 8 each independently represents a substituted or unsubstituted hydrocarbon group having 1 to 12 carbon atoms, and m represents an integer of 0 to 3.
[0053] R 8The substituted or unsubstituted hydrocarbon group represented by the formula (I) is not particularly limited, and examples thereof include alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, and dodecyl groups; cycloalkyl groups such as cyclopentyl and cyclohexyl groups; aryl groups such as phenyl, tolyl, xylyl, and naphthyl groups; aralkyl groups such as benzyl, 2-phenylethyl, and 2-phenylpropyl groups; and halogenated alkyl groups such as chloromethyl, 3,3,3-trifluoropropyl, and 3-chloropropyl groups.
[0054] Among these, the amino-modified organopolysiloxane A2 is preferably an organopolysiloxane having a linear structure with an amino group-containing group at the end or in the side chain, or an organopolysiloxane having a linear structure with a hydroxyl group at the end and an amino group-containing group in the side chain. By using such an amino-modified organopolysiloxane A2, the reactivity of the first agent and the second agent tends to be further improved.
[0055] The amino functional equivalent of the amino group of the amino-modified organopolysiloxane A2 is preferably 100 to 8000 g / mol, more preferably 200 to 6000 g / mol, more preferably 300 to 4000 g / mol, and even more preferably 300 to 2000 g / mol. When the amino functional equivalent is within the above range, the reactivity of the first agent and the second agent is improved, and the uniform reactivity tends to be improved.
[0056] The viscosity of the amino-modified organopolysiloxane A2 at 25° C. is preferably 5 to 2000 mm 2 / s, more preferably 5 to 1750 mm 2 / s, and more preferably 5 to 1500 mm 2 When the viscosity is within the above range, the handleability of the two-component curing composition set tends to be improved.
[0057] In addition, the amino-modified organopolysiloxane A2 preferably further has a hydroxyl-containing group in which a hydroxyl group is bonded to a silicon atom. The bonding position of the hydroxyl-containing group is not particularly limited, and may be at the end or the side chain, or at the end and the side chain. Among these, the amino-modified organopolysiloxane A2 having a linear structure with amino-containing groups at both ends is preferred. By using such an amino-modified organopolysiloxane A2, the compatibility with the epoxy-modified organopolysiloxane A1 is further improved, and the uniform reactivity tends to be further improved.
[0058] (Thermal conductive filler B2) The thermally conductive filler B2 is, for example, a filler having a thermal conductivity of 10 W / m·K or more, and may be the same as the thermally conductive filler B1. Among these, it is preferable to include at least one selected from the group consisting of aluminum oxide, aluminum nitride, boron nitride, silicon nitride, zinc oxide, aluminum hydroxide, metallic aluminum, magnesium oxide, copper, silver, and diamond. By using such a thermally conductive filler B2, the filling property is improved, and the thermal conductivity of the obtained cured product tends to be further improved. These thermally conductive fillers B2 may be used alone or in combination of two or more.
[0059] The average particle size and content of the thermally conductive filler B2 may be the same as those of the thermally conductive filler B1, and the above descriptions regarding the thermally conductive filler B1 may be read and applied to the thermally conductive filler B2.
[0060] (Additives) In addition, the types and contents of polydimethylsiloxane C, organosilane D, and colorant E that may be contained in the second agent are the same as those of the first agent described above, and the descriptions regarding these in the first agent can be read and applied as those regarding the second agent, so duplicated descriptions will be omitted here.
[0061] The thermally conductive filler, polydimethylsiloxane, organosilane, and colorant as the second agent and the thermally conductive filler, polydimethylsiloxane, organosilane, and colorant as the first agent may be of the same type or of different types.
[0062] <Ratio of first and second agent> In the two-component curing composition set of this embodiment, the ratio of the epoxy-modified organopolysiloxane A1 in the first agent and the amino-modified organopolysiloxane A2 in the second agent can be appropriately set according to the epoxy group content of the epoxy-modified organopolysiloxane A1 in the first agent and the amino group content of the amino-modified organopolysiloxane A2 in the second agent. Epoxy group content = epoxy-modified organopolysiloxane A1 content / functional group equivalent Amino group content = Amino-modified organopolysiloxane A2 content / Functional group equivalent
[0063] The ratio of epoxy group content / amino group content satisfied by the combination of the first agent and the second agent is preferably 70 / 30 to 10 / 90, more preferably 55 / 45 to 20 / 80. When the ratio of epoxy group content to amino group content is within the above range, uniform reactivity is improved, and a cured product with a sufficiently formed crosslinked structure can be obtained.
[0064] <Application> The thermal conductivity of the mixture of the first and second parts after curing, measured in accordance with ASTM D5470, is preferably 1.0 W / mk or more, and more preferably 2.0 W / mk or more. Such a two-component curing composition set of the present embodiment can be suitably used as a thermally conductive heat dissipating material.
[0065] [Cured product] The cured product according to this embodiment can be obtained, for example, by mixing the first and second parts in the two-part curing composition set described above. More specifically, the cured product (crosslinked cured product) is obtained by mixing the first and second parts in a mixture obtained by mixing the first and second parts, and an addition reaction between the epoxy group of the epoxy-modified organopolysiloxane A1 contained in the first part and the amino group of the amino-modified organopolysiloxane A2 contained in the second part progresses to form a three-dimensional network structure having crosslinked bonds, thereby obtaining the cured product.
[0066] The cured product of the present embodiment may be molded into a desired shape after mixing the first and second parts. In addition, since the cured product of the present embodiment contains a thermally conductive filler, it can be suitably used as a thermally conductive heat dissipation material.
[0067] For mixing, a mixer such as a roll mill, kneader, Banbury mixer, or line mixer is used, and examples of the method include a method of kneading using a universal mixer, hybrid mixer, Trimix (manufactured by Inoue Seisakusho), or a static mixer. The molding method is preferably a doctor blade method, but depending on the viscosity of the resin, an extrusion method, a press method, or a calendar roll method can be used. The reaction conditions for the progression of the addition reaction are not particularly limited, but are usually performed at room temperature (e.g., 25°C) to 150°C for 0.1 to 24 hours.
[0068] The mixing ratio of the first agent and the second agent can be appropriately set depending on the type of the first agent and the second agent used and the purpose of use, but for example, the volume ratio of first agent:second agent may be 1.5:1.0 to 1.0:1.5, or may be 1.0:1.0.
[0069] [Electronic equipment] The electronic device of the present embodiment includes an electronic component, the above-mentioned cured product, and a housing that houses the electronic component and the cured product, the electronic component and the housing being in contact with each other via the cured product.
[0070] Here, the electronic components are not particularly limited, and examples thereof include heat-generating electronic components such as motors, battery packs, circuit boards sold for in-vehicle power systems, power transistors, and microprocessors. Further, the metal housing is not particularly limited, and examples thereof include heat sinks configured for heat dissipation or heat absorption, etc.
Example
[0071] Hereinafter, the present invention will be described in more detail with reference to examples, but the present invention is not limited to the following examples.
[0072] [First Agent] The following components A1 to C1 were mixed based on the compounding ratios (parts by weight) shown in Table 1 to prepare first agents I-1 to I-3. The mixing of each component was performed using a hybrid mixer ARE-310 (manufactured by Shinchi Co., Ltd., trade name).
[0073] <Component A1: Organopolysiloxane> A1-1: DOWSIL BY 16-839 Fluid (manufactured by Dow Corning Toray Co., Ltd., trade name), epoxy-modified organopolysiloxane, viscosity at 25°C: 6000 mm 2 / s, functional group equivalent of epoxy group: 3700 g / mol, alicyclic type (ethylcyclohexene oxide group), epoxy group bonding position: side chain A1-2: DOWSIL BY 8411 Fluid (manufactured by Dow Corning Toray Co., Ltd., trade name), epoxy-modified organopolysiloxane, viscosity at 25°C: 8000 mm 2 / s, functional group equivalent of epoxy group: 3300 g / mol, aliphatic type (glycidyl group), epoxy group bonding position: side chain A1-3: DOWSIL SE 1885A (manufactured by Dow Corning Toray Co., Ltd., trade name) organopolysiloxane having a vinyl group (containing a platinum catalyst)
[0074] <Component B1: Thermal Conductive Filler> B1-1: Spherical alumina, average particle size: 45 μm, DAW45S (manufactured by Denka Co., Ltd., trade name), thermal conductivity 35 W / mK B1-2: Spherical alumina, average particle size: 5 μm, DAW05 (manufactured by Denka Co., Ltd., trade name), thermal conductivity 35 W / mK
[0075] <Component C1: Colorant> C1: Resin Black #442 (manufactured by Resino Color Kogyo Co., Ltd., trade name)
[0076]
Table 1
[0077] [Second Agent] The following A2 component to B2 component were mixed based on the blending ratios (parts by weight) shown in Table 2 to prepare Second Agents II-1 to II-6. The mixing of each component was carried out using a hybrid mixer ARE-310 (manufactured by Shin Kee Co., Ltd., trade name).
[0078] <Component A2: Organopolysiloxane> A2-1: DOWSIL BY 16-213 (manufactured by Dow Corning Toray Co., Ltd., trade name), amino-modified organopolysiloxane, viscosity at 25°C: 60 mm 2 / s, functional group equivalent of amino group: 2700 g / mol, primary amine (3-aminopropyl group), amino group bonding position: side chain A2-2: DOWSIL BY 16-853U (manufactured by Dow Corning Toray Co., Ltd., trade name), amino-modified organopolysiloxane, viscosity at 25°C 14 mm 2 / s, functional group equivalent of amino group 450 g / mol, primary amine (3-aminopropyl group), amino group bonding position: terminal A2-3: DOWSIL BY 16-892 (manufactured by Dow Corning Toray Co., Ltd., trade name), amino-modified organopolysiloxane, viscosity at 25°C 1400 mm 2 / s, functional group equivalent of amino group 1900 g / mol, primary amine and secondary amine (aminoethylaminopropyl group), amino group bonding position: side chain, both terminals OH-containing A2-4: A mixture of an organopolysiloxane having a vinyl group and an organopolysiloxane having a hydrosilyl group, DOWSIL SE 1885B (manufactured by Dow Corning Toray Co., Ltd., trade name) A2-5: DOWSIL BY 8428 Fluid (manufactured by Dow Corning Toray Co., Ltd., trade name), carbinol-modified organopolysiloxane, viscosity at 25°C: 140 mm 2 / s, functional group equivalent: 1600 g / mol A2-6: DOWSIL BY 16-880 Fluid (manufactured by Dow Corning Toray Co., Ltd., trade name), carboxyl-modified organopolysiloxane, viscosity at 25°C: 2500 mm 2 / s, functional group equivalent: 3300 g / mol
[0079] <Component B2: Thermally conductive filler> B2-1: Spherical alumina, average particle size: 45 μm, DAW45S (manufactured by Denka Co., Ltd., trade name) B2-2: Spherical alumina, average particle size: 5 μm, DAW05 (manufactured by Denka Co., Ltd., trade name)
[0080]
Table 2
[0081] <Thermal conductivity> Using a resin material thermal resistance measuring device manufactured by Hitachi Technologies, Ltd., the thermal conductivity of the thermally conductive cured product was measured by a method conforming to ASTM D5470. Specifically, the mixture obtained by mixing the first agent and the second agent in the volume ratio described in each example and comparative example was molded into thicknesses of 0.2 mm, 0.5 mm, and 1.0 mm, respectively. Each of the obtained molded products was held at 25°C for 24 hours to allow the curing reaction to proceed, and a thermally conductive cured product was obtained. For the obtained thermally conductive cured product, the thermal resistance value of each was measured with a measurement area of 10 mm × 10 mm. The slope of the straight line obtained with the thermal resistance value on the vertical axis and the thickness of the thermally conductive cured product on the horizontal axis was calculated and taken as the thermal conductivity of the thermally conductive cured product.
[0082] [Measurement of average particle size] The average particle size of the thermally conductive filler was measured using a laser diffraction particle size distribution analyzer SALD-20 (product name) manufactured by Shimadzu Corporation. For the evaluation sample, 50 ml of pure water and 5 g of the thermally conductive filler powder to be measured were added to a glass beaker, stirred with a spatula, and then dispersed in an ultrasonic cleaner for 10 minutes. The solution of the dispersed thermally conductive filler powder was added drop by drop to the sampler part of the device using a dropper, and measurement was performed when the absorbance stabilized. In the laser diffraction particle size distribution analyzer, the particle size distribution is calculated from the data of the light intensity distribution of the diffraction / scattering holes by the particles detected by the sensor. The average particle size is calculated by multiplying the measured particle size value by the relative particle amount (difference %) and dividing it by the total relative particle amount (100%). The average particle size is the average diameter of the particles, and can be calculated as the cumulative weight average value D50 (or median diameter), which is the maximum value or peak value. The D50 is the particle size with the highest occurrence rate.
[0083] [Cured product] The first and second parts obtained above were mixed in the combinations and volume ratios shown in Tables 3 and 4 to obtain mixtures. The mixtures obtained were held at 150°C for 1 hour to allow the curing reaction to proceed, and cured products were obtained. The curing reaction was evaluated according to the following methods. The evaluation results are summarized in Tables 3 and 4.
[0084] <Evaluation of uniform reactivity> The mixture of the first and second parts was molded into a shape of about 5 mm thick and 2 cm long and wide, and was held at 150°C for 1 hour to allow the curing reaction to proceed, yielding a cured product. Differences in the cured state depending on the location of the obtained cured product were confirmed, and whether the curing reaction had proceeded uniformly throughout the entire cured product (uniform reactivity) was evaluated according to the following criteria. (Evaluation Criteria) ◎: Completely cured, with the center and edges having the same hardness 〇: Completely cured, but the center was slightly softer than the edges. ×: Not cured
[0085] <Evaluation of high temperature stability> The first and second agents were each stored in a heated state in a dryer at 60° C. for 7 days. The first and second agents after the heated storage were mixed in the same manner as above and kept at 150° C. for 1 hour to allow the curing reaction to proceed. The cured state at that time was confirmed, and whether the first and second agents had curing performance even after the heated storage (high temperature stability) was evaluated according to the following criteria. (Evaluation Criteria) ○: Hardened ×: Not cured
[0086] [Table 3]
[0087] [Table 4]
[0088] As is clear from Tables 3 and 4 above, the two-component curing composition sets of the present invention in Examples 1 to 6 had good mixability and uniform reactivity, and were excellent in storage stability.
[0089] Comparative Example 1 was a two-component curing composition set of the addition reaction type using a platinum catalyst, and therefore the catalyst was deactivated when stored at high temperatures, resulting in poor storage stability.
[0090] Comparative Example 2 was a mixture of an epoxy-modified organopolysiloxane and a carbinol-modified organopolysiloxane, but no cured product was formed and evaluation was not possible.
[0091] Comparative Example 3 was a mixture of an epoxy-modified organopolysiloxane and a carboxyl-modified organopolysiloxane, but no cured product was formed and evaluation was not possible.
[0092] Examples 5 and 6 had better uniform reactivity than Examples 1 and 3, which were substantially the same conditions except for the type of amino-modified organopolysiloxane in the second agent. Examples 5 and 6 differ from Examples 1 and 3 in that an amino-modified organopolysiloxane modified with OH groups at both ends was used in the second agent. This confirmed that it is more preferable to use an amino-modified organopolysiloxane modified with OH groups at both ends. [Industrial Applicability]
[0093] The two-component curing thermally conductive grease composition of the present invention has industrial applicability as a thermally conductive cured product obtained by mixing and curing the first and second parts, in particular as a thermally conductive grease material used to thermally bond a heating element and a metal housing.
Claims
1. A first agent including an epoxy-modified organopolysiloxane A1 having an epoxy group-containing group and a thermally conductive filler B1; A second agent including an amino-modified organopolysiloxane A2 having an amino group-containing group and a thermally conductive filler B2; The content of the thermally conductive filler B1 is 400 to 3,000 parts by weight per 100 parts by weight of the epoxy-modified organopolysiloxane A1, The content of the thermally conductive filler B2 is 400 to 3,000 parts by weight per 100 parts by weight of the epoxy-modified organopolysiloxane A2, The thermally conductive filler B1 and the thermally conductive filler B2 each contain at least one selected from the group consisting of aluminum oxide, aluminum nitride, boron nitride, silicon nitride, zinc oxide, aluminum hydroxide, metallic aluminum, magnesium oxide, copper, silver, and diamond, each of which has a thermal conductivity of 10 W / m·K or more. Two-part curing composition set.
2. the functional group equivalent weight of the epoxy group in one molecule of the epoxy-modified organopolysiloxane A1 is 100 to 11,000 g / mol; The two-component curing composition set according to claim 1 .
3. the functional group equivalent weight of the amino group in one molecule of the amino-modified organopolysiloxane A2 is 100 to 8000 g / mol; The two-component curing composition set according to claim 1 or 2.
4. The amino-modified organopolysiloxane A2 in the second agent has hydroxyl group-containing groups at both ends. The two-component curing composition set according to any one of claims 1 to 3.
5. The first agent does not contain an organopolysiloxane having at least a vinyl group at the end or in a side chain, and an organopolysiloxane having at least a hydrosilyl group at the end or in a side chain; and The second agent is provided with an organopolysiloxane having at least a vinyl group at the end or in a side chain, and the second agent does not include an organopolysiloxane having at least a hydrosilyl group at the end or in a side chain. The two-component curing composition set according to any one of claims 1 to 4.
6. The thermal conductivity of the mixture of the first agent and the second agent after curing, measured in accordance with ASTM D5470, is 1.0 W / mK or more. The two-component curing composition set according to any one of claims 1 to 5.
7. Used as a thermally conductive heat dissipation material, The two-component curing composition set according to any one of claims 1 to 6.
8. The two-component curing composition set according to any one of claims 1 to 7, wherein the first component and the second component are mixed together, cured product.
9. Used as a thermally conductive heat dissipation material, The cured product according to claim 8.
10. An electronic component, the cured product according to claim 9, and a housing that houses the electronic component and the cured product, The electronic component and the housing are in contact with each other via the cured product. electronic equipment.
Citation Information
Patent Citations
Two-component pouring sealant and preparation method thereof
CN107325782A
Siliconeeepoxy resin composition
JP1980090554A
Liquid silicone rubber composition
JP1985179417A
Preparation of metal-graphite laminated material
JP1994321518A
Curable organopolysiloxane composition
JP1996269337A